Wavelet decomposition and embeddings of generalised Besov–Morrey spaces. (January 2022) - Haroske, Dorothee D.; Moura, Susana D.; Skrzypczak, Leszek
Abstract: We study embeddings between generalised Besov–Morrey spaces N φ, p, q s ( R d ) . Both sufficient and necessary conditions for the embeddings are proved. Embeddings of the Besov–Morrey spaces into the Lebesgue spaces L r ( R d ) are also considered. Our approach requires a wavelet characterisation of the spaces which we establish for the system of Daubechies wavelets.